Evaluation of Monoclonal Antibodies to vWf Antigen for Use in Autoradiographing vWf Multimer Analysis - Enayat, M S; Hill, F G H; Robinson, W; Prowse, C V; Hornsey, V S (Thrombosis and Haemostasis, 1987)
Nine monoclonal antibodies (MAb, coded ESvWF 1-5, 7-10) to human von Willebrand’s factor (vWf) have been studied for their labelling characteristics with 125I and their ability to demonstrate vWf multimers by autoradiography after discontinuous SDS electrophoresis on agarose and agarose/acrylamide gels in plasma from normal and von Willebrand’s disease (vWD) patients. Of ESvWF 1, 2, 4, 7, 8 and 9, ESvWF 2 gave autoradiographs most similar to those obtained with a polyclonal antibody. The others gave much fainter staining of all bands suggesting that the epitope detected by ESvWF 2 is either more common or, less easily altered by SDS than the epitopes identified by the other MAb’s. ESvWF 2 gave a different staining pattern with a IIC vWD patient than that obtained using a polyclonal antibody. The most striking result, however, was shown by ESvWF 3, 5 and 10 which failed to stain the lower band of the lower molecular weight multimer. This suggests that the lower triplet band, unlike the central and upper bands of the triplet, does not contain the epitope identified by these three MAb’s. With these reagents it has been possible to show, for the first time, that epitope differences do exist between the constituent bands of the vWf triplet.
Keywords: Monoclonal antibodies; vWf antigen; Autoradiography; Multimeric analysis